Cardiorespiratory and metabolic responses during maximal and submaximal eggbeater kicking by water polo players - Sasaki, Y.; Takagi, H.; Fujii, N.; Tsuji, B.; Tsubakimoto, S.; Nishiyasu, T. (16th annual ECSS Congress Liverpool/UK, July 6-9 2011, 2011)
During a water polo match, players float in the water and perform the eggbeater kick (EK) for about 1 h. The intensity of the EK depends on the situation and is especially high during contact play. The purpose of this study was to investigate the cardiorespiratory and metabolic responses during maximal and submaximal EK exercises in water polo players. Methods Thirteen male college-age competitive water polo players performed incremental cycling (C) and EK exercises in random order. Both exercises consisted of n•3-min exercises with 60-s recoveries until exhaustion. During EK, subjects were not allowed to use arm sculling. Results We found that VO2peak was significantly lower during EK than C (48.9±6.8 vs. 53.6±4.9 ml/kg/min, p<0.05), as was VEpeak (102.3±16.5 vs. 135.8 ± 15.2 l/min, p<0.05). We also compared heart rate (HR), minute ventilation (VE), tidal volume (TVE), and respiratory rate (RR) between EK and C at three levels of VO2 (24, 36 and 48 ml/kg/min). Although HRs at all three VO2 levels did not significantly differ between the exercises, VEs at all three VO2 levels were significantly lower during EK than C. In addition, TVEs were significantly greater during EK than C at the two lower VO2 levels, while RRs were significantly lower. Discussion We found VO2peak during EK to be 91% of that during C in water polo players. It may be that active leg muscle mass during EK was smaller than during C. Additionally, because VEpeak was lower during EK, arterial O2 content also may have been lower, contributing to the lower VO2peak. VEs at three levels of VO2 were lower during EK than C. Given that the thermal conductivity of water is greater than that of air, and that VE increases with increases in core temperature during exercise (Hayashi et al. 2006), the lower VE during EK may reflect a lower core temperature. We also found that TVEs at the two lower VO2 levels were significantly greater during EK than C, while RRs were lower. Because buoyancy in a resting vertical position increases with increases in TVE (Von Döbeln et al. 1974), the subjects may have increased their buoyancy during EK by increasing TVE. If so, not only their leg movement (Sanders, 1999) but also their breathing is important for keeping their upper body above the water surface during EK.